KEBIMBANGAN IDENTITAS DALAM SASTRA MUSLIM TURKI DAN IMIGRAN DI EROPA DAN AMERIKA DALAM KARYA MY NAME IS RED OLEH ORHAN PAMUK, LIRIK DARI MUSIK SAMI YUSUF, DAN THE TRANSLATION OF THE QUR'AN OLEH YUSUF ALI - Rahma Safira; Ridho Nurfadhilah; Nurholis Nurholis (Cahaya Ilmu Bangsa Institute, 2024)
Abstract This paper explores the identity confusion experienced by Muslim communities, particularly from Turkey and Muslim immigrants in Europe and America, as reflected in their literature and art. The identity of the Muslim diaspora often stands at the crossroads between Islamic tradition and secular Western modernity. Through the analysis of works such as My Name Is Red by Orhan Pamuk, the lyrics of Sami Yusuf's music, and the translation of the Qur'an by Yusuf Ali, this study delves into how Muslim artists articulate their identity struggles in their works. A sociological literature approach is used to examine how social and political dynamics shape the identity formation of the Muslim diaspora. Keywords: Literature, Identity, Muslim Literature, immigrants Abstrak Jurnal ini mengeksplorasi kebimbangan identitas yang dialami oleh komunitas Muslim, khususnya dari Turki dan imigran Muslim di Eropa dan Amerika, yang tercermin dalam karya sastra dan seni. Identitas diaspora Muslim sering kali berada di persimpangan antara tradisi Islam dan modernitas Barat yang sekuler. Melalui analisis karya seperti